Advancing Partner Notification Through Electronic Communication Technology: A Review of Acceptability and Utilization Research. Issue 6 (2nd June 2016) - Pellowski, Jennifer; Mathews, Catherine; Kalichman, Moira O.; Dewing, Sarah; Lurie, Mark N.; Kalichman, Seth C.
Abstract : A cornerstone of sexually transmitted infection (STI) prevention is the identification, tracing, and notification of sex partners of index patients. Although partner notification reduces disease burden and prevents new infections as well as reinfections, studies show that only a limited number of partners are ever notified. Electronic communication technologies, namely, the Internet, text messaging, and phone calls (i.e., e-notification), have the potential to expand partner services. We conducted a systematic review of studies that have investigated the acceptability and utility of e-notification. We identified 23 studies that met the following criteria: (a) 9 studies presented data on the acceptability of technology-based communications for contacting sex partner(s), and (b) 14 studies reported on the utilization of communication technologies for partner notification. Studies found high levels of interest in and acceptability of e-notification; however, there was little evidence for actual use of e-notification. Taken together, results suggest that electronic communications could have their greatest impact in notifying less committed partners who would otherwise be uninformed of their STI exposure. In addition, all studies to date have been conducted in resource-rich countries, although the low cost of e-notification may have its greatest impact in resource-constrained settings. Research is needed to determine the best practices for exploiting the opportunities afforded by electronic communications for expanding STI partner services.